2019
DOI: 10.1177/0192513x19878864
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Behaviors across the Transition to Parenthood

Abstract: The transition to parenthood (TTP) often is associated with declines in couple relationship satisfaction. The current study evaluated changes in three relationship behaviors, namely communication, dyadic coping and relationship self-regulation, across the TTP and the association of those behaviors with relationship satisfaction. One hundred and three couples completed questionnaires twice before and three times after the birth of their first child. Prenatally, all behaviors were stable, except negative communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Common dyadic coping was associated with better perceived couple adjustment among women (Donato et al, 2009; Molgora et al, 2018). Furthermore, the effect of men’s antenatal common dyadic coping on women’s postpartum couple adjustment (partner effect) confirms the study of Rauch-Anderegg et al (2019), which has already found a significant association between male behaviors and women’s well-being. This finding is coherent with other studies that reported gender variations in the relational influence of dyads, with women more sensible to their partners (Martins et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Common dyadic coping was associated with better perceived couple adjustment among women (Donato et al, 2009; Molgora et al, 2018). Furthermore, the effect of men’s antenatal common dyadic coping on women’s postpartum couple adjustment (partner effect) confirms the study of Rauch-Anderegg et al (2019), which has already found a significant association between male behaviors and women’s well-being. This finding is coherent with other studies that reported gender variations in the relational influence of dyads, with women more sensible to their partners (Martins et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…These studies underscore the crucial role of common dyadic coping for couple adjustment for the perinatal period, confirming findings of numerous previous studies on couples facing other stressors. Only one contribution (Rauch-Anderegg et al, 2019) investigated dyadic coping across the transition to parenthood: the longitudinal study by Rauch-Anderegg et al found that positive relationship behaviors decreased in both mothers and fathers during the postpartum. The study also illustrated patterns of influence among new parents, with males’ negative dyadic coping predicting their own relationship satisfaction, and their supportive dyadic coping behaviors being associated with new mothers’ relationship satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth, confinement, breastfeeding, job suspension, diminishing independence and reduced personal freedom make women more sensitive to their partner’s characteristics. A supportive partner’s approach helps them get over these changes more easily ( Rauch-Anderegg et al, 2020 ), while a stressed, unsupportive, depressed or an anxious spouse impacts the individual’s marital satisfaction ( Don and Mickelson, 2014 ) and makes the transition more difficult. Although some data shows that the mother’s behavior had no impact on the father’s marital satisfaction ( Rauch-Anderegg et al, 2020 ), it seems that some latent variables of the mothers have a substantial impact.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to our prediction, mothers’ and partners’ CDC were not linked to the other parent’s sexual distress. There is robust evidence for the association between one’s own perceived CDC and both one’s own and a partner's relational outcomes (Austin & Falconier, 2013; Falconier, 2013; Zemp, Milek, Cummings, & Bodenmann, 2017), including new parents’ marital adjustment (Molgora, Acquati, et al., 2019; Rauch‐Anderegg, Kuhn, Milek, Halford, & Bodenmann, 2020). However, our findings are in line with the limited past research that has found an association between one’s own perceived dyadic coping and one’s own sexual satisfaction, but not a partner’s sexual adjustment (Van Schoors et al., 2019).…”
Section: Discussionmentioning
confidence: 99%